Effect of Ultraviolet Irradiation on the Survival of Simian Virus 40 Functions in Human and Mouse Cells - Aaronson, Stuart A. (1970)
The relative sensitivities to ultraviolet light of various simian virus 40 (SV40) functions were studied in human and mouse cells. Transformation appeared to be less ultraviolet (UV)-sensitive than either T or V antigen when all functions were compared in the same cell. However, the time course of both T- and V-antigen appearance was delayed with UV-irradiated virus, so that the survival curves of these functions changed with time. Mouse and human cells which were transformed by UV-SV40 all contained SV40 T antigen. Infectious virus could be recovered from many more transformants than would be expected from the infectivity in African green monkey kidney cells of the irradiated virus. The results suggest that human and mouse cells are capable of reactivating UV-damaged SV40.